2014
DOI: 10.1177/1078155214541571
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan dosing (Q6 or Q24) with adjusted or actual body weight, does it matter?

Abstract: Further prospective studies are warranted to elucidate which weight is most likely to achieve goal AUC and subsequent optimal patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Except that using adjusted weight to calculate pre-targeted doses required more frequent increments according to pharmacokinetics in both dosing schedules. (26) These studies confirmed that when using target dosing for Bu, both dosing schedules are equivalent. These smaller studies support the findings of our study that represent contemporary clinical practices in North America.…”
Section: Discussionsupporting
confidence: 59%
“…Except that using adjusted weight to calculate pre-targeted doses required more frequent increments according to pharmacokinetics in both dosing schedules. (26) These studies confirmed that when using target dosing for Bu, both dosing schedules are equivalent. These smaller studies support the findings of our study that represent contemporary clinical practices in North America.…”
Section: Discussionsupporting
confidence: 59%
“…Other isoenzymes (GSTM1, GSTT1, and GSTP1) are involved in the metabolism of Bu but to a much lower extent. 6,7 The glutathione family has a high rate of polymorphisms, and this is believed to contribute to 20%-95% of the variation seen in Bu pharmacokinetics. 8 The impact of glutathione S-transferase (GST) polymorphisms on the clinical outcomes of hematopoietic stem cell transplantation (HSCT) is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the food intake and reduction of body weight is observed in patients with myeloid leukemia who are treated with Butene dimethylsulphonate (Bulsufan). In addition to belonging to the same family, Bulsufan has a very similar chemical structure to EDS, which may have influenced the food intake alteration of animals treated with EDS Clemmons et al 2014). Despite the reduction in body weight, no alterations were observed in the weight of most target-organs of animals treated with EDS, demonstrating that this compound did not promote systemic toxicological effects, since it has already been established that the variation of the weight of these organs can be used as parameter of toxicity (Sellers et al, 2007;Wolfsegger et al, 2009).…”
Section: -Discussionmentioning
confidence: 99%